A REVIEW OF ACORUS CALAMUS (VACHA) AS PER ANCIENT ASPECT & RECENT ADVANTAGES WITH PHARMACOTHERAPEUTIC PROPERTIES - Dr. Mayukh Sharma, Dr. Priya K. Pillai Dr. Swathi K.S. (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2018)
Acorus calamus is a useful medicinal plant that has proven to be beneficial in a variety of medical fields. This study examines the various pharmacological activities of plants using various extracts or solvents. In humans, this herb enhances the capacity of intelligence and self-expression. Acorus calamus comes in a variety of forms, each of which has anti-inflammatory, anti-spasmodic, anti-protective, and anti-hepatotoxic properties. The article also discusses the numerous Acorus calamus products on the market. The rhizome of the Calamus (Acorus calamus Linn., Araceae) plant, also known as sweet flag or Vacha, is an aromatic herb native to Central Asia and Eastern Europe. It has been used by the Ayurvedic practitioners since time immemorial for diseases ranging from weakness of memory to being used as an anthelminthic. Keywords - Acorus calamus, Vacha, Ayurveda, Pharmacotherapeutic Properties.